2017
DOI: 10.1371/journal.pone.0176685
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality and later sleep timing are risk factors for osteopenia and sarcopenia in middle-aged men and women: The NEO study

Abstract: ContextSleep deprivation has detrimental metabolic consequences. Osteopenia and sarcopenia usually occur together and increase risk of fractures and disease. Results from studies linking sleep parameters to osteopenia or sarcopenia are scarce and inconsistent.ObjectiveTo examine the associations of sleep parameters with osteopenia and sarcopenia, considering the influence of sex and menopause.Design, setting and participantsCross-sectional analysis of 915 participants (45–65 years, 56% women, BMI 26 (range: 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 52 publications
3
78
2
1
Order By: Relevance
“…Another study including community‐dwelling very old adults (>80 years) and applying actigraphy measures found that higher bedtime variability (a measure of sleep pattern variation) was independently related to reduced lean mass and increased fat mass . Circadian rhythm disruptions are increasingly frequent with aging and can impact body composition negatively .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study including community‐dwelling very old adults (>80 years) and applying actigraphy measures found that higher bedtime variability (a measure of sleep pattern variation) was independently related to reduced lean mass and increased fat mass . Circadian rhythm disruptions are increasingly frequent with aging and can impact body composition negatively .…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, other sleep‐related measures have been isolatedly associated with either obesity or sarcopenia in middle‐aged and older adults . However, no study has evaluated the associations of sleep with obesity and/or sarcopenia using simultaneously different sleep assessment methods and including polysomnography (PSG), the gold‐standard test for the diagnosis of OSA.…”
Section: Introductionmentioning
confidence: 99%
“…With sleep disorder as the dependent variable and sarcopenia as the explanatory variable, we calculated the adjusted odds ratio for sarcopenia with regard to sleep disorder using the logistic regression analysis. On clinical diagnosis, variables to be adjusted were age, BMI, HbA1c level, smoking, alcohol consumption, number of comorbidities (hypertension, dyslipidemia, diabetic retinopathy, diabetic neuropathy, diabetic nephropathy and cardiovascular disease), depression, cognitive impairment and living alone, according to previous studies . The significance level (two‐tailed) was <0.05, and we used Stata version 12.0 (StataCorp, College Station, TX, USA) for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A study that targeted older individuals living in an area reported an association between sarcopenia and sleep disorder . However, to the best of our knowledge, there is no study on the association between sarcopenia and sleep disorders in older patients with diabetes using SARC‐F‐J.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation